Influence of different additives on properties of cement based composites reinforced with eucalyptus kraft pulp - Silva, Danillo Wisky (2018)
The extrusion process has been gaining prominence in the production of fiber cement. This process presents several advantages in the production line compared to the conventional process, such as: fiber orientation, lower water / cement ratio, lower implantation cost and good mechanical performance of the composites. However, due to the compaction that occurs during the process, the composites generated are denser when compared to the composites produced by other processes. The objectives of this study were to produce, characterize and evaluate the behavior of extruded cementitious composites with different concentrations of hydrated superabsorbent polymer (SAP) and commercial air-entraining. Cement composites were produced with Portland cement CPV-ARI, limestone, SAP, hydroxypropyl methylcellulose (HPMC) and polyether carboxylic acid (ADVA 175). Cement composites with different SAP concentrations (0.5, 1.0, 1.5, and 2.0%) were produced and evaluated after 28 days of curing and after 30 cycles of accelerated aging. The same cementitious matrix SAP, Darafill 300 EXP air incorporator, Drycast air incorporator, brown Kraft pulp of Eucalyptus spp., HPMC and ADVA 175 were used for the production of the fiber cement. The fiber cements with different concentrations of SAP (0.3, 0.5 and 0.7%), Darafill (0.6, 0.8 and 1.2%) and Drycast (0.6 and 1.2%) were evaluated after 28 days of cure. SAP was efficient in the incorporation of air in cementitious composites without reinforcement and in fiber cement, however, there was formation of millimetric voids, substantially reducing the mechanical performance of the materials. After accelerated aging, all non-reinforced composites showed equivalent reduction in mechanical performance. The fiber cement, despite the degradation of the fibers, were more resistant to the aging cycles. The surfactants did not incorporate air in the cements as expected, however, due to the increased wettability, there was an effective hydration of the dry cement grains, which resulted in higher mechanical performance, higher density, lower porosity and lower voids in the interior of the cementitious matrix. In general, fiber cements with SAP are less dense and presented lower mechanical performance in comparison with the control fiber cement, which restricts their application to non-structural materials. However, the use of surfactants, although it does not incorporate air in the cements, may be interesting, due to the increase in the mechanical performance in extruded fiber cement.